DNA damage levels in peripheral blood mononuclear cells before and after first cycle of chemotherapy have comparable prognostic values in germ cell tumor patients - Ivovič, Danica; Šestáková, Zuzana; Roška, Jan; Kálavská, Katarína; Hurbanová, Lenka; Holíčková, Andrea; Smolková, Božena; Kabelíková, Pavlína; Novotná, Věra; Chovanec, Michal; Palacka, Patrik; Mego, Michal; et al. (Frontiers in Oncology, 2024)
Background: Germ cell tumours (GCTs) represent the most frequent solid malignancy in young men. This malignancy is highly curable by cisplatin (CDDP)-based chemotherapy. However, there is a proportion of patients having a poor prognosis due to refractory disease or its relapse. No reliable biomarkers being able to timely and accurately stratify poor prognosis GCT patients are currently available. Previously, we have shown that chemotherapy-naïve GCT patients with higher DNA damage levels in peripheral blood mononuclear cells (PBMCs) have significantly worse prognosis compared to patients with lower DNA damage levels.Methods: DNA damage levels in PBMCs of both chemotherapy-naïve and first cycle chemotherapy-treated GCT patients have been assessed by standard alkaline comet assay and its styrene oxide (SO)-modified version. These levels were correlated with clinico-pathological characteristics.We re-confirm prognostic value of DNA damage level in chemotherapy-naïve GCT patients and reveal that this prognosticator is equally effective in GCT patients after first cycle of CDDP-based chemotherapy. Furthermore, we demonstrate that SO-modified comet assay, due to its ability to detect DNA cross-links, is far more sensitive compared to standard alkaline comet assay in case of patients who underwent first cycle of CDDP-based chemotherapy.We propose that DNA damage levels in PBMCs before and after first cycle of CCDP-based chemotherapy are comparable independent prognosticators for progression-free and overall survivals in GCT patients. Therefore, their clinical use is highly advised to stratify GCT patients to identify those who are most at risk of developing disease recurrence or relapse, allowing tailoring therapeutic interventions to poor prognosis individuals, and optimizing their care management and treatment regimen.